Immune-inflammatory, neuroplastic, and epigenetic effects of electroconvulsive therapy in mood disorders: an overview of recent studies - João, Rafael Batista; Toiansk de Azevedo, João Paulo Rocha Pereira; Pereira, Dácio Almeida; Ragazzo, Paulo César; de Oliveira, Paulo Maurício (Frontiers in Psychiatry, 2025)
BackgroundElectroconvulsive therapy (ECT) remains an effective intervention for severe and treatment-resistant mood disorders, particularly major depressive disorder (MDD) and bipolar disorder (BD). While traditionally linked to neurotransmitter modulation, recent research suggests that ECT exerts broader biological effects. Currently, there is a necessity for identifying factors that could support a more accurate selection of individuals, predict their therapeutic response, and help investigate evidence of possible neuroplastic effects of this technique. In this setting, many studies have been published in the last few years, aiming to identify potential biomarkers by understanding immune-inflammatory, structural, and cellular mechanisms and their correlations with clinical outcomes post-ECT.MethodsWe searched PubMed, Embase, Scopus, Web of Science, PsycINFO, and Cochrane Library for studies published between 2020 and 2025. Studies were selected based on their relevance to inflammatory, immune, structural, and cellular mechanisms associated with ECT.ResultsTwenty-six studies were included. The main results reported post-ECT reductions in inflammatory markers, including C-reactive protein, interleukin-6, and tumor necrosis factor-alpha, or suggested a biphasic trajectory, with an initial transient immune activation preceding inflammatory partial resolution. Noteworthy differences were related to age, as younger patients showed more favorable immune adaptability in comparison with older individuals, who demonstrated elongated inflammatory activity. Neuroplastic changes following ECT were observed, including increased hippocampal neurogenesis, enhanced brain-derived neurotrophic factor expression, and structural changes in neuroimaging studies. Novel exploratory research on post-mortem analyses further confirmed the upregulation of neuroplasticity markers without evidence of sustained neuroinflammation. In addition, epigenetic mechanisms, particularly microRNA modulation following ECT, may induce long-term cellular reprogramming, potentially influencing treatment response. Moreover, one recent study suggested that elevated baseline levels of miR-223-3p may be a predictor of ECT response among treatment-resistant depression patients. Finally, a recent study exploring mitochondrial adaptations found that the interactions between mitochondrial DNA copy number, oxidative stress, and ECT remain inconclusive.ConclusionRecent studies have expanded the understanding of ECT’s neuroinflammation effects and beyond, adding data on its interactions with immune, neuroplastic, and genetic mechanisms in human samples. Although many gaps still exist, these findings pave the way for further research that may improve outcomes of treatment-resistant mood disorders.